Flexibility of Custom Design over Simplex Lattice Design in Co-Processed Excipient Formulations - Aris Perdana Kusuma (Science and Technology Indonesia, 2018)
Custom design is a modeling technique that puts forward the custom formula on the pharmaceutical formula optimization. The components may be adjusted to the formula constraints. However, these designs sometimes do not accommodate all the components used. In addition, its effectiveness is not necessarily optimal when compared with standard designs such as simplex lattice design (SLD). This study used microcrystalline cellulose PH 101 (MCC PH 101), lactose and K30 kollidon which were computerized. Custom design and SLD compared with Design Expert software based on previous research data. Tablet hardness and tapping index were used as test parameters to assess design effectiveness. The optimal formula result obtained was MCC PH 101: lactose: kollidon K30 80% each: 10%: 10% for SLD. This value differs from custom designs that get results in the absence of lactose proportions. Custom design prediction results actually get better value than SLD for tablet hardness and tapping index.